Indole-3-carbinol attenuates lipopolysaccharide-induced acute respiratory distress syndrome through activation of AhR: role of CCR2+ monocyte activation and recruitment in the regulation of CXCR2+ neutrophils in the lungs - Holloman, Bryan Latrell; Wilson, Kiesha; Cannon, Alkeiver; Nagarkatti, Mitzi; Nagarkatti, Prakash S. (Frontiers in Immunology, 2024)
Indole-3-carbinol (I3C) is found in cruciferous vegetables and used as a dietary supplement. It is known to act as a ligand for aryl hydrocarbon receptor (AhR). In the current study, we investigated the role of AhR and the ability of I3C to attenuate LPS-induced Acute Respiratory Distress Syndrome (ARDS). To that end, we induced ARDS in wild-type C57BL/6 mice, Ccr2gfp/gfp KI/KO mice (mice deficient in the CCR2 receptor), and LyZcreAhRfl/fl mice (mice deficient in the AhR on myeloid linage cells). Additionally, mice were treated with I3C (65 mg/kg) or vehicle to investigate its efficacy to treat ARDS. I3C decreased the neutrophils expressing CXCR2, a receptor associated with neutrophil recruitment in the lungs. In addition, LPS-exposed mice treated with I3C revealed downregulation of CCR2+ monocytes in the lungs and lowered CCL2 (MCP-1) protein levels in serum and bronchoalveolar lavage fluid. Loss of CCR2 on monocytes blocked the recruitment of CXCR2+ neutrophils and decreased the total number of immune cells in the lungs during ARDS. In addition, loss of the AhR on myeloid linage cells ablated I3C-mediated attenuation of CXCR2+ neutrophils and CCR2+ monocytes in the lungs from ARDS animals. Interestingly, scRNASeq showed that in macrophage/monocyte cell clusters of LPS-exposed mice, I3C reduced the expression of CXCL2 and CXCL3, which bind to CXCR2 and are involved in neutrophil recruitment to the disease site. These findings suggest that CCR2+ monocytes are involved in the migration and recruitment of CXCR2+ neutrophils during ARDS, and the AhR ligand, I3C, can suppress ARDS through the regulation of immune cell trafficking.